History of Asthma From Childhood and Arterial Stiffness in Asymptomatic Young Adults: The Bogalusa Heart Study. Issue 5 (May 2018) - Sun, Dianjianyi; Li, Xiang; Heianza, Yoriko; Nisa, Hoirun; Shang, Xiaoyun; Rabito, Felicia; Kelly, Tanika; Harville, Emily; Li, Shengxu; He, Jiang; Bazzano, Lydia; Chen, Wei; et al.
Abstract : Asthma is related to various cardiovascular risk. Whether a history of asthma from childhood contributes to arterial stiffness in adulthood, a noninvasive surrogate for cardiovascular events, is unknown. Prospective analyses were performed among 1746 Bogalusa Heart Study participants aged 20 to 51 years with data on self-report asthma collected since childhood. Aorta–femoral pulse wave velocity (af-PWV, m/s) was repeatedly assessed among adults ≥aged 18 years. Generalized linear mixed models and generalized linear models were fitted for the repeated measurements of af-PWV and its changes between the last and the first measurements, respectively. After a median follow-up of 11.1 years, participants with a history of asthma from childhood had a higher af-PWV (6.78 versus 6.13; P =0.048) and a greater increase in af-PWV (8.99 versus 2.95; P =0.043) than those without asthma, adjusted for age, sex, race, smoking status, heart rate, body mass index, systolic blood pressure, lipids, and glycemia. In addition, we found significant interactions of asthma with body mass index and systolic blood pressure on af-PWV and its changes ( P for interaction <0.01). The associations of asthma with af-PWV and its changes appeared to be stronger among participants who were overweight and obese (body mass index ≥25 kg/m 2 ) or with prehypertension and hypertension (systolic blood pressure ≥120 mm Hg) compared with those with a normal body mass index or systolic blood pressure. Our findings indicate that a history of asthma from childhood is associated with higher af-PWV and greater increases in af-PWV, and such associations are stronger among young adults who are overweight or with elevated blood pressure.